Experience of skin disease and relationships with healthcare providers. (3rd June 2019) - Gilhooley, E.; Daly, S.; Gallagher, O.; Glacken, M.; McKenna, D.
Summary: A number of inequalities exist between members of the Travelling community and the general population, including health inequality. A number of obstacles to engagement with health services exist: experience or perception of discrimination, cultural barriers and health literacy (understanding health information) barriers. A positive relationship with healthcare providers can help improve the health of members of the Travelling community. The objective of this study, which was conducted in Ireland, was to explore Travellers' experience of skin disease and their relationship with healthcare providers. The data was collected using focus groups of female members of the Irish Travelling community with experience of skin health issues. Three focus groups were held at three separate locations in the West of Ireland, with 10 participants in each group. Themes were identified from focus group transcripts. Themes included health literacy, discrimination, information inconsistency, trust and communication. We identified a number of factors that determined the quality of interactions between members of the Travelling community and their healthcare providers, as well as potential opportunities to enhance these relationships. The demonstration of 'cultural competence' positively impacted the quality of relationships; this means integrating cultural, social or community based beliefs and behaviours with the healthcare a person receives. A preference towards secondary or specialist services (e.g. hospital or consultant‐led, rather than GP‐level care) emerged from our focus groups; similar preferences have been shown in others studies where secondary care services have gained recognition for their non‐discriminatory approach. Factors that helped to create positive relationships included: an appreciation of varying degrees of health literacy, the provision of sufficient information tailored to an individual's needs, and a demonstration of cultural competence. Dermatologists are well placed to provide practical, customised treatment guidance, while integrating patients' culturally based beliefs.  Abstract : Linked Article:  Gilhooley et al. Br J Dermatol 2019; 180 :1405–1411